Self-healing PC with high refractive index and preparation method and application thereof

By adding NASC and terephthalisothiocyanate in the synthesis of polycarbonate (PC), the molecular structure is modified, and the problem of insufficient refractive index and scratch resistance characteristics of PC lenses is solved, and high refractive index and self-refractive index are achieved. The healing effect simplifies the processing process and reduces costs.

CN119463149AActive Publication Date: 2025-02-18WANHUA CHEM GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411697101.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-18
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

As a lens material, polycarbonate (PC) has problems with insufficient refractive index and scratch resistance. The existing coating solutions increase process complexity and cost, while affecting refractive index and transmittance, and exist. Risk of shedding.

Method used

By adding NASC third monomer and terephthalisothiocyanate during PC synthesis, the molecular structure of PC is modified to improve its refractive index, and to heal itself by heat treatment when the surface of the product is scratched. .

Benefits of technology

The high refractive index of PC has been increased to above 1.8, and at the same time, more than 90% of the surface morphology of the product can be restored under low temperature heat treatment, simplifying the processing process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005152361020000021
    Figure BDA0005152361020000021
  • Figure FDA0005152361010000011
    Figure FDA0005152361010000011
Patent Text Reader

Abstract

The invention provides self-healing PC with high refractive index and a preparation method and application thereof. A self-healing monomer and a refractive functional monomer are introduced in the preparation process of the self-healing PC. According to the self-healing PC with the high refractive index, the refractive index of the PC is further improved; meanwhile, the defect that PC is easily scratched and damaged is overcome, and self-healing of a PC notch can be achieved at the temperature of 40 DEG C or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a self-healing PC with a high refractive index and a preparation method and application thereof. Background Art

[0002] As an engineering plastic, polycarbonate (PC) is widely used in electronics, automobiles, construction, optics and other fields. Polycarbonate itself has good mechanical properties such as tensile strength, as well as excellent optical properties. In terms of lens applications, the cost is low, but limited by its low refractive index, it is currently widely used in the field of medical goggles.

[0003] In addition, if PC is used as a lens, there is a problem of weak scratch resistance. The surface of PC parts is often scratched, resulting in poor performance. This can currently be solved by coating the PC substrate, but at the same time it will make the production process more complicated, further increasing the processing cost of PC lenses. After coating, there is a risk of affecting the refractive index, transmittance, and falling off over time.

[0004] Therefore, there is still a need to develop a new type of high refractive index PC that can further increase the refractive index while making the scratched morphology easy to recover. Summary of the invention

[0005] The purpose of the present invention is to provide a self-healing PC with a high refractive index. By adding NASC third monomer and p-phenylene diisothiocyanate during the PC synthesis process, the molecular structure of PC is modified, which greatly improves the high refractive index of PC and can also restore the surface morphology of the product to its original state through a heat treatment method when the surface of the product is scratched.

[0006] Another object of the present invention is to provide a preparation method and application of the self-healing PC with a high refractive index.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0008] A self-healing PC with a high refractive index has the following structural formula:

[0009]

[0010] Wherein R1 is NASC, the molecular formula is CO(NH)2COCHCH2, and R2 is monophenol.

[0011] In a preferred embodiment, the refractive index of the high refractive index self-healing PC of the present invention can be increased to above 1.8, preferably above 2, for example 2, 2.1, 2.2, 2.3, 2.4, etc., and the self-repair rate can be increased to above 90%, preferably above 95%, and more preferably above 99%.

[0012] On the other hand, the aforementioned method for preparing a high refractive index self-healing PC comprises the following steps:

[0013] 1) mixing bisphenol A and alkali solution to obtain a homogeneous aqueous solution a;

[0014] 2) adding an oil-soluble solvent to the homogeneous aqueous solution a to obtain an oil-water mixture b;

[0015] 3) continuously introducing phosgene and alkali solution into the oil-water mixture b to react;

[0016] 4) adding p-phenylene diisothiocyanate, NASC, p-tert-butylphenol and a catalyst, and continuously introducing an alkali solution, and continuing the reaction for a period of time to obtain a PC reaction solution;

[0017] 5) Taking the oil phase of the PC reaction solution, removing the oil-soluble solvent after acid washing and water washing to obtain PC solid.

[0018] In some specific embodiments, in step 1), the mass concentration of bisphenol A in the homogeneous aqueous solution a is 10-20wt%, such as 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, etc.;

[0019] The alkali solution is an aqueous solution of NaOH and / or KOH, and the mass concentration of the alkali solution in the homogeneous aqueous solution a is 4-7wt%, such as 4wt%, 5wt%, 6wt%, 7wt%, etc.

[0020] In some specific embodiments, in step 2), the oil-soluble solvent can be one or more of chloroform, tetrachloroethane, dichloromethane, chlorobenzene, tetrahydrofuran, dioxane, and pyridine, and the mass ratio of the homogeneous aqueous solution a to the oil-soluble solvent is 0.5-1.5, for example, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, etc., preferably 0.9-1.1.

[0021] In some specific embodiments, in step 3), the molar ratio of phosgene to bisphenol A is 1-2, for example, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, etc.

[0022] In step 3), the alkali solution is an aqueous solution of NaOH and / or KOH with a mass concentration of 5wt%-50wt%, for example 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc., and is introduced at a flow rate of 1-10g / min during the reaction, for example, at a flow rate of 1g / min, 2g / min, 3g / min, 4g / min, 5g / min, 6g / min, 7g / min, 8g / min, 9g / min, 10g / min, etc.

[0023] In step 3), the reaction temperature is 15°C-36°C, for example, 16°C, 18°C, 19°C, 20°C, 25°C, 28°C, 30°C, 33°C, 35°C, 36°C, etc.; the reaction time is 5-10 min, for example, 6 min, 7 min, 8 min, 9 min, 10 min, etc.

[0024] In some specific embodiments, in step 4), preferably, the catalyst is triethylamine or a quaternary ammonium salt, such as N,N,N,N-trimethylbenzyl ammonium chloride, N,N,N,N-dimethylethyl octadecyl ammonium sulfate, more preferably triethylamine, and the content of the catalyst in the reaction solution of step (4) is 50-500ppm, for example, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, etc.

[0025] In step 4), the molar ratio of p-phenylene diisocyanate to bisphenol A is 0.01 to 0.08, for example, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, etc.; the molar ratio of NASC to bisphenol A is 0.01 to 0.05, for example, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, etc.; the molar ratio of p-tert-butylphenol to bisphenol A is 0 to 0.08, for example, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, etc.

[0026] In step 4), the alkali solution is an aqueous solution of NaOH and / or KOH, preferably an aqueous solution of NaOH, and more preferably the same as the alkali solution in step 3); the mass concentration of the alkali solution is 5wt%-50wt%, for example, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc., preferably 32%; during the reaction, the alkali solution is introduced at a flow rate of 0.1-1g / min, for example, at a flow rate of 1g / min, 2g / min, 3g / min, 4g / min, 5g / min, 6g / min, 7g / min, 8g / min, 9g / min, 10g / min, etc.

[0027] In step 4), preferably, the reaction temperature is controlled in the range of 25°C-36°C, for example, 25°C, 28°C, 30°C, 33°C, 35°C, 36°C, etc.; preferably, the reaction time is 5-40min, for example, 6min, 7min, 8min, 9min, 10min, 15min, 20min, 25min, 30min, 35min, 40min, etc.

[0028] In some specific embodiments, in step 5), the oil phase of the PC reaction solution can be obtained by conventional technical means in the art, such as separation after standing and stratification, or by extraction and other methods, without special restrictions. In the present invention, the acid used for pickling can be a strong acid substance such as hydrochloric acid, sulfuric acid, nitric acid, etc., preferably hydrochloric acid, and the mass concentration of the acid can be 0.5wt%-10wt%, such as 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, etc., preferably 1wt%. There is no special restriction on the number of pickling and water washing, such as 2-5 times. After water washing, the oil-soluble solvent is removed, such as by flash evaporation to remove the solvent, to obtain PC solid, the catalyst content in the solid product is less than 0.3ppm, the chloride ion content is less than 10ppm, and the oil-soluble solvent content is less than 100ppm.

[0029] In the present invention, the molecular structure of PC is modified by adding NASC as a third monomer during the synthesis of PC, wherein NASC is a substance with a high hydrogen bond density. After being introduced into PC, when the surface of the product is scratched, the surface morphology of the product can be restored to its original state by a heat treatment method, and the required temperature is relatively low. More importantly, in order to further enhance the high refractive index capability of PC, p-phenylene diisothiocyanate is introduced during the synthesis of PC. This method can greatly improve the high refractive index capability of PC. After the refractive capacity is improved, the PC lens or lens can be made thinner under the same refractive effect, which greatly expands the application field of PC in lenses and greatly improves the application experience.

[0030] In another aspect of the present invention, the aforementioned self-healing PC with a high refractive index or the self-healing PC with a high refractive index prepared by the aforementioned preparation method is used in the fields of optical devices, lasers, LEDs, etc.

[0031] Compared with the prior art, the present invention has the following advantages:

[0032] 1) The high refractive index self-healing PC material of the present invention greatly improves the refractive ability of PC by introducing p-phenylene diisothiocyanate into the PC molecular chain.

[0033] 2) Due to the addition of NASC photosensitive monomer in the high refractive index self-healing PC material of the present invention, after the surface of the PC product is scratched, the scratched surface morphology of the product can be restored to its original state through low-temperature heat treatment at 40-60°C.

[0034] 3) Compared with the prior art, the present invention is the first to prepare a new type of self-healing PC with a high refractive index, and optimizes the molecular structure of PC. Compared with the currently commonly used coating technology, it has stronger stability and is easier to process. DETAILED DESCRIPTION

[0035] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.

[0036] The main sources of raw materials involved in the following examples are as follows:

[0037] The NASC reference patent "A supramolecular copolymer hydrogel and its preparation method" (paragraph 0020 of CN112521550A) was used for preparation.

[0038] The remaining materials, unless otherwise specified, can be purchased from the market.

[0039] The test methods involved in the following embodiments are as follows:

[0040] The refractive index test refers to the standard QB / T 2506-2017, and the refractive index of the sample is tested using an Abbe refractometer (model: WYA-2S) at a test wavelength of 587.56nm.

[0041] Repair rate test: Prepare tensile specimens according to GB / T 1040-1992, use a blade to scratch a 1mm deep scratch in the middle of the neck, use a WDW-05 electronic mechanical stretching machine (China Times Group Co., Ltd.) to perform a tensile test on the samples of the control group at room temperature, and then use ultraviolet light to irradiate the tensile specimens with the same scratching for 10 minutes and then perform the same tensile test, record the tensile strength of different samples, test three times and take the average value. Self-healing efficiency (HE) is an important parameter to measure the self-healing performance of materials. The specific calculation formula is as follows: Among them, S H represents the tensile strength of the PC spline in the experimental group, and S0 represents the tensile strength of the PC spline in the control group.

[0042] [Example 1]

[0043] Add 540g of deionized water to a 2L jacketed reactor under nitrogen protection, then add 31g of solid NaOH and stir to dissolve. Adjust the temperature to 32°C, add 80g of bisphenol A solid, stir for 30min until bisphenol A is completely dissolved, and obtain a homogeneous aqueous solution;

[0044] Add 650g of dichloromethane to the reactor and adjust the speed to 300r / min to mix the water phase and the oil phase evenly;

[0045] 9.4 L of phosgene gas was introduced into the reactor at a rate of 0.94 L / min, and 32 wt% of NaOH lye was added into the reactor at a rate of 1.9 g / min, during which the reaction temperature was controlled at 35°C;

[0046] Add 4 g of p-phenylene diisocyanate, 3 g of NASC, 7.5 g of 10 wt% PTBP solution, and 78 ppm of triethylamine to the reactor. At the same time, add 32 wt% NaOH solution to the reactor at a rate of 0.28 g / min. Stir continuously for 30 min and then stop. During this period, control the reaction temperature at 28 °C.

[0047] After the water and oil phases were separated, the oil phase was first washed with 1.5% HCl solution, and then washed with deionized water until the water after washing was neutral. Then, the MC was removed and dried to obtain PC solid;

[0048] It was pressed into a 3mm plate using a flat vulcanizer at 300℃ and kept warm for 40 minutes. The test refractive index was 2.3 and the repair rate was 99%.

[0049] [Example 2]

[0050] Add 540g of deionized water to a 2L jacketed reactor under nitrogen protection, then add 31g of solid NaOH and stir to dissolve. Adjust the temperature to 32°C, add 80g of bisphenol A solid, stir for 30min until bisphenol A is completely dissolved, and obtain a homogeneous aqueous solution;

[0051] Add 650g of chlorobenzene to the reactor and adjust the speed to 300r / min to mix the water phase and the oil phase evenly;

[0052] 9.4 L of phosgene gas was introduced into the reactor at a rate of 0.94 L / min, and 32 wt% of NaOH lye was added into the reactor at a rate of 1.9 g / min, during which the reaction temperature was controlled at 35°C;

[0053] Add 2.5 g of p-phenylene diisothiocyanate, 1 g of NASC, 2.3 g of 10 wt% PTBP solution, and 78 ppm of triethylamine to the reactor. At the same time, add 32 wt% NaOH solution to the reactor at a rate of 0.28 g / min. Stir continuously for 30 min and then stop. During this period, control the reaction temperature at 28 °C.

[0054] After the water and oil phases were separated, the oil phase was first washed with 1.5% HCl solution, and then washed with deionized water until the water after washing was neutral. Then, the MC was removed and dried to obtain PC solid;

[0055] It was pressed into a 3mm plate using a flat vulcanizer at 300℃ and kept warm for 40 minutes. The test refractive index was 2 and the repair rate was 98%.

[0056] [Example 3]

[0057] Add 540g of deionized water to a 2L jacketed reactor under nitrogen protection, then add 31g of solid NaOH and stir to dissolve. Adjust the temperature to 32°C, add 80g of bisphenol A solid, stir for 30min until bisphenol A is completely dissolved, and obtain a homogeneous aqueous solution;

[0058] Add 650g of chloroform to the reactor and adjust the speed to 300r / min to mix the water phase and the oil phase evenly;

[0059] 9.4 L of phosgene gas was introduced into the reactor at a rate of 0.94 L / min, and 32 wt% of NaOH lye was added into the reactor at a rate of 1.9 g / min, during which the reaction temperature was controlled at 35°C;

[0060] Add 1 g of p-phenylene diisocyanate, 0.6 g of NASC, 4.7 g of 10 wt% PTBP solution, and 78 ppm of triethylamine to the reactor. At the same time, add 32 wt% NaOH solution to the reactor at a rate of 0.28 g / min. Stir continuously for 30 min and then stop. During this period, control the reaction temperature at 28 °C.

[0061] After the water and oil phases were separated, the oil phase was first washed with 1.5% HCl solution, and then washed with deionized water until the water after washing was neutral. Then, the MC was removed and dried to obtain PC solid;

[0062] It was pressed into a 3mm plate using a flat vulcanizer at 300℃ and kept warm for 40 minutes. The test refractive index was 1.9 and the repair rate was 96%.

[0063] [Example 4]

[0064] Add 540g of deionized water to a 2L jacketed reactor under nitrogen protection, then add 31g of solid NaOH and stir to dissolve. Adjust the temperature to 32°C, add 80g of bisphenol A solid, stir for 30min until bisphenol A is completely dissolved, and obtain a homogeneous aqueous solution;

[0065] Add 650g of tetrahydrofuran into the reactor and adjust the speed to 300r / min to mix the water phase and the oil phase evenly;

[0066] 9.4 L of phosgene gas was introduced into the reactor at a rate of 0.94 L / min, and 32 wt% of NaOH lye was added into the reactor at a rate of 1.9 g / min, during which the reaction temperature was controlled at 35°C;

[0067] Add 0.5 g of p-phenylene diisocyanate, 2 g of NASC, 4.7 g of 10 wt% PTBP solution, and 78 ppm of triethylamine to the reactor. At the same time, add 32 wt% NaOH solution to the reactor at a rate of 0.28 g / min. Stir continuously for 30 min and then stop. During this period, control the reaction temperature at 28 °C.

[0068] After the water and oil phases were separated, the oil phase was first washed with 1.5% HCl solution, and then washed with deionized water until the water after washing was neutral. Then, the MC was removed and dried to obtain PC solid;

[0069] It was pressed into a 3mm plate using a flat vulcanizer at 300℃ and kept warm for 40 minutes. The test refractive index was 1.8 and the repair rate was 99%.

[0070] [Comparative Example 1]

[0071] Add 540g of deionized water to a 2L jacketed reactor under nitrogen protection, then add 31g of solid NaOH and stir to dissolve. Adjust the temperature to 32°C, add 80g of bisphenol A solid, stir for 30min until bisphenol A is completely dissolved, and obtain a homogeneous aqueous solution;

[0072] Add 650g of dichloromethane to the reactor and adjust the speed to 300r / min to mix the water phase and the oil phase evenly;

[0073] 9.4 L of phosgene gas was introduced into the reactor at a rate of 0.94 L / min, and 32 wt% of NaOH lye was added into the reactor at a rate of 1.9 g / min, during which the reaction temperature was controlled at 35°C;

[0074] Add 4 g of p-phenylene diisocyanate, 7.5 g of 10 wt% PTBP solution, and 78 ppm of triethylamine to the reactor. At the same time, add 32 wt% NaOH solution to the reactor at a rate of 0.28 g / min. Stir continuously for 30 min and then stop. During this period, control the reaction temperature at 28 °C.

[0075] After the water and oil phases were separated, the oil phase was first washed with 1.5% HCl solution, and then washed with deionized water until the water after washing was neutral. Then, the MC was removed and dried to obtain PC solid;

[0076] It was pressed into a 3mm plate using a flat vulcanizer at 300℃ and kept warm for 40 minutes. The test refractive index was 2.1 and the repair rate was 0.

[0077] [Comparative Example 2]

[0078] Add 540g of deionized water to a 2L jacketed reactor under nitrogen protection, then add 31g of solid NaOH and stir to dissolve. Adjust the temperature to 32°C, add 80g of bisphenol A solid, stir for 30min until bisphenol A is completely dissolved, and obtain a homogeneous aqueous solution;

[0079] Add 650g of dichloromethane to the reactor and adjust the speed to 300r / min to mix the water phase and the oil phase evenly;

[0080] 9.4 L of phosgene gas was introduced into the reactor at a rate of 0.94 L / min, and 32 wt% of NaOH lye was added into the reactor at a rate of 1.9 g / min, during which the reaction temperature was controlled at 35°C;

[0081] Add 3 g of NASC, 7.5 g of 10 wt% PTBP solution, and 78 ppm of triethylamine to the reactor. At the same time, add 32 wt% NaOH solution to the reactor at a rate of 0.28 g / min. Stir continuously for 30 min and then stop. During this period, control the reaction temperature at 28 °C.

[0082] After the water and oil phases were separated, the oil phase was first washed with 1.5% HCl solution, and then washed with deionized water until the water after washing was neutral. Then, the MC was removed and dried to obtain PC solid;

[0083] It was pressed into a 3mm plate using a flat vulcanizer at 300℃ and kept warm for 40 minutes. The test refractive index was 1.6 and the repair rate was 90%.

[0084] The applicant declares that the present invention illustrates the two-component polyurethane thermal conductive structural adhesive and its preparation method through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A self-healing PC with a high refractive index, characterized in that: The structural formula is as follows: Wherein R1 is NASC, the molecular formula is CO(NH)2COCHCH2, and R2 is monophenol; Preferably, the refractive index of the self-healing PC is above 1.8, and the self-repair rate is above 90%.

2. The method for preparing the self-healing PC with high refractive index according to claim 1, characterized in that: The following steps are involved: 1) mixing bisphenol A and alkali solution to obtain a homogeneous aqueous solution a; 2) adding an oil-soluble solvent to the homogeneous aqueous solution a to obtain an oil-water mixture b; 3) continuously introducing phosgene and alkali solution into the oil-water mixture b to react; 4) adding p-phenylene diisothiocyanate, NASC, p-tert-butylphenol and a catalyst, and continuously introducing an alkali solution, and continuing the reaction for a period of time to obtain a PC reaction solution; 5) Taking the oil phase of the PC reaction solution, removing the oil-soluble solvent after acid washing and water washing to obtain PC solid.

3. The preparation method according to claim 2, characterized in that: In step 1), the mass concentration of bisphenol A in the homogeneous aqueous solution a is 10-20 wt %; and / or The alkali solution is an aqueous solution of NaOH and / or KOH, and the mass concentration of the alkali solution in the homogeneous aqueous solution a is 4-7 wt %.

4. The preparation method according to claim 2 or 3, characterized in that: In step 2), the oil-soluble solvent is selected from one or more of chloroform, tetrachloroethane, dichloromethane, chlorobenzene, tetrahydrofuran, dioxane, and pyridine; Preferably, the mass ratio of the homogeneous aqueous solution a to the oil-soluble solvent is 0.5-1.

5.

5. The preparation method according to any one of claims 2 to 4, characterized in that: In step 3), the molar ratio of phosgene to bisphenol A is 1-2; and / or The alkali solution is an aqueous solution of NaOH and / or KOH with a mass concentration of 5wt%-50wt%, and is introduced at a flow rate of 1-10g / min during the reaction.

6. The preparation method according to claim 5, characterized in that: The reaction time is 5-10 minutes.

7. The preparation method according to any one of claims 2 to 6, characterized in that: In step 4), the molar ratio of p-phenylene diisocyanate to bisphenol A is 0.01-0.08; the molar ratio of NASC to bisphenol A is 0.01-0.05, and the molar ratio of p-tert-butylphenol to bisphenol A is 0.02-0.

08.

8. The preparation method according to claim 7, characterized in that: In step 4), the catalyst is triethylamine and / or quaternary ammonium salt; Preferably, the amount of the catalyst added is 50-500 ppm of the mass of the reaction solution in step 3).

9. The preparation method according to any one of claims 2 to 6, characterized in that: In step 4), the alkali solution is an aqueous solution of NaOH and / or KOH with a mass concentration of 5wt%-50wt%, and is introduced at a flow rate of 1-10g / min during the reaction; Preferably, the reaction time is 5-40 min.

10. Application of the high refractive index self-healing PC according to claim 1 or the high refractive index self-healing PC prepared by the preparation method according to any one of claims 2 to 9 in the fields of optical devices, lasers, and LEDs.

Citation Information

Patent Citations

  • Preparation method of efficient PEI (polyethyleneimine) modified porous adsorption material and application

    CN106861658A

  • Ultra-high-toughness resin lens and preparation method thereof

    CN108219109A

  • Supramolecular copolymerized hydrogel and preparation method thereof

    CN112521550A

  • Preparation method of novel notch-impact-resistant photosensitive PC, and application of novel notch-impact-resistant photosensitive PC in sunscreen

    CN113683734A